Encontros Bibli Vol. 16, n.32 (2011) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2013)
Encontros Bibli Vol. 16, n.32 (2011)Link de acesso ao númerohttp://www.periodicos.ufsc.br/index.php/eb/issue/view/1642/showToc